Biotransformation of albendazole and activities of selected detoxification enzymes in Haemonchus contortus strains susceptible and resistant to anthelmintics - Vokřál, Ivan; Jirásko, Robert; Stuchlíková, Lucie; Bártíková, Hana; Szotáková, Barbora; Lamka, Jiří; Várady, Marián; Skálová, Lenka (Veterinary parasitology, 2013)
The increased activity of drug-metabolizing enzymes can protect helminths against the toxic effect of anthelmintics. The aim of this study was to compare the metabolism of the anthelmintic drug albendazole (ABZ) and the activities of selected biotransformation and antioxidant enzymes in three different strains of Haemonchus contortus: the ISE strain (susceptible to common anthelmintics), the BR strain (resistant to benzimidazole anthelmintics) and the WR strain (multi-resistant). H. contortus adults were collected from the abomasum of experimentally infected lambs. In vitro (subcellular fractions of H. contortus homogenate) as well as ex vivo (living nematodes cultivated in flasks with medium) experiments were performed. HPLC with spectrofluorimetric and mass-spectrometric detection was used in the analysis of ABZ metabolites. The in vitro activities of oxidation/antioxidation and conjugation enzymes toward model substrates were also assayed. The in vitro data showed significant differences between the susceptible (ISE) and resistant (BR, WR) strains regarding the activities of peroxidases, catalase and UDP-glucosyltransferases. S-oxidation of ABZ was significantly lower in BR than in the ISE strain. Ex vivo, four ABZ metabolites were identified: ABZ sulphoxide and three ABZ glucosides. In the resistant strains BR and WR, the ex vivo formation of all ABZ glucosides was significantly higher than in the susceptible ISE strain. The altered activities of certain detoxifying enzymes might partly protect the parasites against the toxic effect of the drugs as well as contribute to drug-resistance in these parasites.
Keywords: Drug Resistance; peroxidasa; ABZ; UDP-glucosyltransferase; Enzyme Activation; molekulární struktura; Molecular Structure; Strain-differences; Peroxidase; ovce; nemoci ovcí; albendazole sulfone; Sheep; léková rezistence; albendazole sulfoxide; Anthelmintics; Catalase; Animals; Sheep Diseases; Drug resistance; anthelmintika; zvířata; albendazol; katalasa; aktivace enzymů; Nematodes; albendazole; Superoxide Dismutase; ABZ-SO; Albendazole; Haemonchus; superoxiddismutasa; ABZ-SO(2)